دور المحكمةالدستورية في حماية الحقوق والحريات - رحمة حكيم; سوسن عيايشية (My University, 2023)
Abstract: Enshrined the principle of the supremacy of the Constitution and the promotion of the status of rights and freedoms, the Constitutional Founder of Constitutional Amendment 2020 has created an independent body called the Constitutional Court, of a judicial nature instead of the Constitutional Council of a political nature, charged with respecting the Constitution, tasked also with powers to maintain the stability of the functioning of institutions and to ensure respect for rights and freedoms. Given to the paramount importance of the topic of rights and freedoms, effective mechanisms and means of protecting them must be in place. The Censorship of the constitutionality of laws is considred one of the most protective pillars aiming at preventing any provision, whether legislative or regulatory, contrary to the Constitution, and is therefore a means of protecting rights and freedoms from any violation or aggression; The constitutional founder has also adopted a mechanism of the exception of unconstitutionality that enables individuals to plea as the unconstitutionality of laws that infringe upon their rights and freedoms as mandated by the Constitution. ............................ الملخص: تكريسا لمبدأ سمو الدستور و تعزيز مكانة الحقوق و الحريات، استحدث المؤسس الدستوري في التعديل الدستوري 2020 هيئة مستقلة تحت مسمى المحكمة الدستورية، ذات طبيعة قضائية بدلا من المجلس الدستوري ذو الطبيعة السياسية، مكلّفة باحترام الدستور، أُسند إليها صلاحيات تمكنها من الحفاظ على استقرار سير نشاط المؤسسات و ضمان احترام الحقوق و الحريات. نظرا للأهمية البالغة التي يكتسيها موضوع الحقوق و الحريات فانه لا بد من وجود آليات ووسائل فعالة لحمايتها، إذ تعتبر الرقابة على دستورية القوانين من أبرز الدعائم الحامية لها،حيث تهدف إلى منع صدور أي نص سواء كان تشريعيا أو تنظيميا مخالف للدستور، لذلك فهي وسيلة لحماية الحقوق و الحريات من أي خرق أو اعتداء؛ كما عمد المؤسس الدستوري إلى تبني آلية الدفع بعدم الدستورية التي تُمكِّن الأفراد من الدفع بعدم دستورية القوانين الماسة بحقوقهم و حرياتهم التي كلفها لهم الدستور. ............................. Résumé : Consacrant le principe de la suprématie de la Constitution et de la promotion du statut des droits et libertés, le fondateur constitutionnel de l’amendement constitutionnel 2020 a créé un organe indépendant appelé la Cour constitutionnelle, de nature judiciaire au lieu du Conseil constitutionnel de nature politique, chargé de respecter la Constitution, chargé également de maintenir la stabilité du fonctionnement des institutions et de veiller au respect des droits et libertés. Compte tenu de l’importance primordiale du sujet des droits et libertés, des mécanismes efficaces et des moyens de les protéger doivent être mis en place. La censure de la constitutionnalité des lois est considérée comme l’un des piliers les plus protecteurs visant à empêcher toute disposition, législative ou réglementaire, contraire à la Constitution, et constitue donc un moyen de protéger les droits et libertés contre toute violation ou agression; Le fondateur constitutionnel a également adopté un mécanisme d’exception d’inconstitutionnalité qui permet aux individus de plaider l’inconstitutionnalité de lois qui portent atteinte à leurs droits et libertés tels que prescrits par la Constitution.